Disc‐Like Silver Nanocluster Ag93 Built with Bicapped Hexagonal Prismatic Ag15 and Ino Decahedral Ag13 Units - Hu, Feng; He, Rui‐Lin; Guan, Zong‐Jie; Liu, Chun‐Yu; Wang, Quan‐Ming (Angewandte Chemie International Edition, 2023)
The reduction of alkynyl‐silver and phosphine‐silver precursors with a weak reducing reagent Ph2SiH2 led to the formation of a novel silver nanocluster [Ag93(PPh3)6(C≡CR)50]3+ (R=4‐CH3OC6H4), which is the largest structurally characterized cluster of clusters. This disc‐shaped cluster has a Ag69 kernel consisting of a bicapped hexagonal prismatic Ag15 unit wrapped by six Ino decahedra through edge‐sharing. This is the first time that Ino decahedra are used as a building block to assemble a cluster of clusters. Moreover, the central silver atom has a coordination number of 14, which is the highest in metal nanoclusters. This work provides a diverse metal packing pattern in metal nanoclusters, which is helpful for understanding metal cluster assembling mechanisms. The largest structurally characterized cluster of clusters [Ag93(PPh3)6(C≡CR)50]3+ (R=4‐CH3OC6H4) is prepared. It is a disc‐shaped structure, its Ag69 kernel consists of a bicapped hexagonal prismatic Ag15 wrapped by six Ino decahedral Ag13 units through edge‐sharing. The central silver atom has an unprecedented high coordination number of 14. This is the first time that Ino decahedra act as building blocks to assemble a supercluster.